'Pro hebraicis exemplaribus et lingua': carta latina inédita de Benito Arias Montano a Gilberto Genebrardo (BNE, Ms. 149) - Dávila Pérez, Antonio (2015)
This article presents the first critical edition and translation into a modern language of a Latin letter from the Spanish humanist Benito Arias Montano (ca. 1525/1527‐ 1598), director of the Antwerp Polyglot Bible, to the French Hebraist Gilbert Genebrard (1535‐‐1597). The writing is an in‐depth apology of the Hebrew language and the Hebrew original of the Bible. In the introductory study, the author presents the background of this undated document, contextualizes the letter within the whole correspondence of Arias Montano and proposes a dating. The importance of this letter lies in the fact that it is a key piece to reconstruct both the personal controversy between Arias Montano and Wilhelmus Lindanus, regarding the Antwerp Polyglot Bible, and the 16th century debates between supporters and opponents of the Hebrew original of the Holy Scripture.
Keywords: Arias Montano, Benito, -- 1527-1598; Genebrardo, Gilberto; Cartas; Lengua latina